Regulation and Supervision: Measuring the Effectiveness of Supervision for Baitul MÄl wa Tamwil - Rifa Berliana Arifin; JM Muslimin; Nurhasanah Nurhasanah (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
Law Number 25 of 1992 concerning Cooperatives places the supervision of BMT under the Ministry of Cooperatives and SMEs. Meanwhile, Law Number 1 of 2013 concerning Microfinance Institutions mandates that the supervisory function of BMTs is under the supervision of the OJK. The two supervisory regulations give rise to a dualism of supervision which results in the emergence of dualism of supervisory regulations in the operation of BMT. This research uses normative research with analytical descriptive research methods and law content analysis equipped with structured interview guidelines. The data used are in the form of laws and regulations related to supervision and data from research objects in West Java, namely BMT Amanah Syariah, BMT Talaga and BMT Ibaadurrahman. The results of this study indicate that there is a supervisory dualism that has an impact on the emergence of disharmony in the supervision regulation in the operation of BMT in West Java. The factors that cause disharmony in supervisory regulations are that there are two basic legal references related to supervision, the legal substance in the supervisory regulations is not in accordance with the characteristics of the BMT, the implementation of supervisory regulations is not optimal and there is no regulation that regulates the legality of BMT. These factors have legal consequences in the form of disharmony of supervisory law on the operationalization of BMT which has a negative impact on the mechanism of establishment, operation, accountability, and reporting by BMT to each supervisory agency. The factors that cause disharmony in supervisory regulations are that there are two basic legal references related to supervision, the legal substance in the supervisory regulations is not in accordance with the characteristics of the BMT, the implementation of supervisory regulations is not optimal and there is no regulation that regulates the legality of BMT.Keywords: Dualism, BMT, Supervision, Cooperatives and MFIs.